Digital curation projects made easy a step-by-step guide for libraries, archives, and museums - Cowick, Carmen 1981- (Rowman & Littlefield, 2018)
Digital Preservation Made Easy outlines simple steps for accomplishing practical digital preservation projects for those with little experience, time, or resources. Following a general introduction, step-by-step guides for completing commonplace digital preservation projects are covered"-- Provided by publisher.